ESTIMATION OF THE LOCAL GAS PIPELINE LONG EXPLOITED STEEL FATIGUE CRACKS SPREAD RESISTANCE CHARACTERISTICS - Федорович, Ігор Ярославович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The characteristics of the fatigue cracks spread resistance in the corrosive environments have been determined for the long exploited steel of the local gas pipeline Pasichna-Dolyna. It is shown that the most dangerous corrosive environment is the groundwater model NS4.